Simulation of 1.3μm Quantum Dot laser by Using Four Levels Rate Equations Model - Hussein H. Warid (University of Thi-Qar Journal of Science, 2019)
By using four-level rate equations model (4LREM), the dynamics of optical gain and output power in 1.3μm quantum dots laser (QD-laser) is investigated. The numerical model of InAs/GaAs (QD-laser) covers four energy levels for electron. In present model, hole dynamics effect, both homogeneous and inhomogeneous broadening effects are ignored. Present results indicate to, a first and second lasing line, corresponding to the ground state, first excited state respectively appears at low bias current with injection current increasing. As a result, the use of the four -level model described above potentially gives a more complete insight into the dynamics of quantum-dot semiconductor lasers. This result very useful for the design of InAs/GaAs QD laser for communications applications.Key Word: Quantum Dot Laser, Rate Equation Model